2016
DOI: 10.1016/j.bmcl.2016.07.058
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the schistosomicidal effect of the extracts, fractions and major 3-hydroxy-2,6-dialkyl-substituted piperidine alkaloids from the flowers of Senna spectabilis (Fabaceae)

Abstract: In this work, we present the in vitro schistosomicidal activity evaluation of the most active dichloromethane fraction (FDm) (ED50=83.5μg/mL) and of a mixture of the major alkaloids ((-)-cassine/(-)-spectaline, C/E) (ED50=37.4μg/mL) from the flowers of Senna spectabilis against adult worms and cercariae. We also demonstrate other toxic effects including paralysis of the adult worms, inhibition of the secretory activity, tegument lesions and cercaricidal activity. In the association test of Praziquantel (PZQ)-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
2
5
0
1
Order By: Relevance
“…Although PZQ is not used to eliminate snail breeding cercariae, this compound was used during the present study as positive control. In agreement with other reports, PZQ causes 100% mortality of S. mansoni and S. japonicum cercariae at concentrations of 1, 8 and 12.5 μg mL −1 between 0.30 and 3 h …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although PZQ is not used to eliminate snail breeding cercariae, this compound was used during the present study as positive control. In agreement with other reports, PZQ causes 100% mortality of S. mansoni and S. japonicum cercariae at concentrations of 1, 8 and 12.5 μg mL −1 between 0.30 and 3 h …”
Section: Discussionsupporting
confidence: 92%
“…48 Although PZQ is not used to eliminate snail breeding cercariae, this compound was used during the present study as positive control. In agreement with other reports, PZQ causes 100% mortality of S. mansoni and S. japonicum cercariae at concentrations of 1, 8 and 12.5 μg mL −1 between 0.30 and 3 h. 30,36,49 CUR toxicity related to other environment organisms was not evaluated in this study; however, CUR showed no toxic effect and systemic abnormalities in a higher dose (1.5 mg) against Labeo rohita fish. 40 A human study demonstrated that CUR is safe at a 2.5 g per day dose.…”
Section: Discussionsupporting
confidence: 91%
“…The MIC value of 100-200 μg/mL is generally acceptable for plant materials [200]. Although the extracts of the parts of the genus Senna could not reach such MIC values, when the bioactive compounds are isolated from the extracts, MIC values decrease, and the antimicrobial properties increase [201]. Some of these bioactive components include stigmasterol, beta-sitosterol, kaempferol, luteolin, santal, alatonal, aloe-emodin, alquinone, chrysophanol, emodin, physcion, rhein, alarone, benzoquinone, coumarin, ellagitannin, naphthalene, phenolic acid, purine, xanthone, and cassine [202].…”
Section: Anti-infectious Activity Of Senna Plantsmentioning
confidence: 99%
“…Numerous studies reported antiprotozoal activities of genus Senna. de Castro et al [201] conducted a study about the schistosomicidal activity of S. spectabilis flower extracts. Schistosoma is an intestinal parasite that causes a chronic disease called Schistosomiasis.…”
Section: Stem-dichloromethanementioning
confidence: 99%
“…Senna spectabilis, commonly known in Colombia as vainillo, is an ornamental fabaceae that derives its name from the Latin spectabilis, which means spectacular (4) . Currently, the vainillo has been studied especially for its leaves and flowers alkaloid content (5)(6)(7) . Alvear et al (8) determined the bromatological composition of the fruit, observing dry matter, crude protein, and crude energy values of 74.9%, 11.3%, and 3.82 Mcal/kg DM, respectively.…”
Section: Introductionmentioning
confidence: 99%